Plastic scintillators for thermal neutrons detection - Nemchenok, I.B.; Gundorin, N.A.; Shevchik, E.A.; Shurenkova, A.A. (Functional Materials, 2013)
The new cadmium and gadolinium-loaded polymethylmethacrylate based plastic scintillators with the mass fraction of the metals up to 2 % and 4 %, respectively, are described in this article. There are presented the techniques of the new materials preparation and their main properties: transmission spectra, light output and thermal neutrons detection efficiency. The light output of Cd -loaded scintillator with 2 % of metal is 67 % relative to the unloaded sample; the light output of Gd -loaded plastic scintillator with 4 % of the metal is reduced to 67.6 %. There is regular increase of the thermal neutrons detection efficiency for the both series of the scintillation materials.